Vulnerabilidade socioeconômica dos bairros e das favelas de Curitiba - Miloca, Silvano Daniel (2024)
To better understand the dynamics and needs of a metropolis and make more assertive decisions, data is needed that highlights the phenomena to be evaluated. Aggregating complex data, from heterogeneous bases and different granularities is a challenge faced by a researcher who decides to study a Brazilian metropolis like Curitiba. This work sought public data from official sources relating to slums, public security, public health, education, income distribution and the age group of neighborhoods in the capital. It presents the geographical location of each favela in Curitiba, the situation of the households, the materials from which the houses are built and the main risks to which their residents are subject. It highlights the lack of an adequate sewage network and presents services at the city’s health centers for pathologies related to the lack of sewage treatment. It relates the occurrence of crimes in the capital’s neighborhoods with the phenomenon of slums. As a result, it generates an index of socioeconomic vulnerability for neighborhoods in Curitiba, using the statistical method of principal component analysis, and concludes that data related to crime are those that have the greatest weight in defining the vulnerability of a neighborhood in Curitiba.